'Something that, actually, I could do': Community education in service of everyday human rights (Concept: The Journal of Contemporary Community Education Practice Theory, 2020)
IntroductionHuman rights are 'struggle' concepts and people engage in this struggle through theory and practice; people encounter prejudice and discrimination as ideas and actions. Although this is often depicted as a dichotomy, our everyday encounters with prejudice and discrimination make it clear that this struggle requires that we dismantle the false divide between theory and practice if we are to truly achieve the rights and freedoms that belong to us. Community education projects that enable people to contribute both ideas and action have much to teach us about how to weave together theory and practice in ways that enable people to contribute to the human rights struggle within local communities. I offer this article as a contribution to this task. In it I analyse participants’ perceptions of their involvement in a method of community education known as The Human Library, and I discuss what these perceptions teach us about community education projects that enable people to contribute their ideas and actions to the human rights struggle.